Quantum Hospitality and Balinese Women’s Role : Integrating Culture, Sustainability, and Gender in Global Tourism - Ni Desak Made Santi Diwyarthi; Luh Putu Citrawati; Made Darmiati; Nyoman Reni Ariasri; Indah Kusumarini (Yayasan Literasi Sains Indonesia, 2026)
Tourism is one of the world’s fastest-growing industries and a major driver of social, cultural, and economic transformation. In Bali, Indonesia, sustainable tourism increasingly relies on integrating local wisdom, gender inclusion, and multi-stakeholder collaboration. This study explores Quantum Hospitality as an emerging framework that combines cultural intelligence, emotional-spiritual values, digital innovation, and sustainability principles. It examines the roles of Balinese women in cultural tourism, the application of the Tri Hita Karana philosophy, and the effectiveness of Pentahelix collaboration (government–academia–business–community–media) in promoting sustainable cultural tourism. A qualitative systematic literature review of 65 global and regional studies published between 2015 and 2024 reveals that Balinese women serve as cultural transmitters, entrepreneurs, and leaders in community-based tourism. Tri Hita Karana provides an ethical foundation for balancing human, environmental, and spiritual relationships. Comparative insights from Bhutan, Thailand, and Costa Rica demonstrate that Bali’s integration of spirituality, women’s empowerment, and multi-stakeholder governance is unique and replicable. The study recommends strengthening gender-responsive tourism programs, standardizing Quantum Hospitality practices, and developing sustainability frameworks adaptable to diverse global destinations.